MRI assessment of local deformations along human medial gastrocnemius muscle fibers on submaximal plantarflexion activity - Karakuzu, Agah. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2015., 2015)
Comprehensive understanding of the mechanical interactions between skeletal muscles within their integral system of connective tissues requires simultaneous quanti cation of the architecture, force and deformation during in-vivo muscle action. For that purpose, magnetic resonance imaging (MRI) along with nonrigid Demons registration were applied together to quantify 3D local deformations. Additionally, di usion tensor imaging (DTI) was utilized to reconstruct 3D muscle ber architecture. Use of such multi-method approach and speci cally designed experimental equipments together enabled the in-vivo quanti cation of local strains along the orientation of the skeletal muscle bers occurring due to activation. The speci c goal of this study was to test the hypothesis that 15% of maximal voluntary isometric contraction (MVIC) of sustained plantar exion results in a serial strain distribution along the muscle bers of medial gastrocnemius (GM) of female subjects (n=5). Results indicate that considerable local lengthening and shortening occurs simultaneously within individual GM tracts (e.g. from 12.4% shortening up to 36.7% lengthening within a single tract) through the muscle.The hypothesis is therefore con rmed. Moreover, a parallel distribution was also found to be heterogeneous. Such ndings are the characteristic indications of myofascial force transmission e ects that highlights the interdependent mechanical functionality of skeletal muscles. To our knowledge, this is the rst study in the literature that enables the evaluation of in-vivo deformations caused by submaximal isometric contraction with respect to the muscle ber orientations of GM. Such experimental work therefore is expected to lay the groundwork for the investigation of in-vivo myofascial force transmission e ects on clinical applications like botulinum toxin treatment and tendon transfer surgery.|Keywords : MRI, tractography, gastrocnemius, in-vivo, myofascial force transmission.
Keywords: Magnetic resonance imaging.; Muscle strength.; Gastrocnemius muscle.